Konsep Ayah Ideal dalam Al-Qur’an dan Relevansinya terhadap Fenomena Fatherless di Indonesia - Abdus Sholeh (Makkah: Journal Of Islamic Studies, 2025)
The phenomenon of fatherlessness has emerged as a significant contemporary social issue, characterized by the absence of fathers not only in physical terms but also in emotional, moral, and educational roles within the family. This condition has become increasingly visible in modern societies, including Indonesia, due to changing family structures, economic pressures, and the reduction of fatherhood to a purely financial function. This article aims to examine the concept of the ideal father as presented in the Qur’an and to analyze its relevance in responding to the phenomenon of fatherlessness. Employing a qualitative approach through library research, this study utilizes the thematic interpretation method (tafsīr mawdū‘ī) to analyze Qur’anic verses related to father–child relationships. The analysis integrates Qur’anic interpretations with contemporary social studies on fatherlessness. The findings reveal that the Qur’an proposes a holistic concept of ideal fatherhood encompassing moral leadership, dialogical communication, emotional protection, spiritual and ethical education, exemplary conduct, and spiritual responsibility within the family. This study argues that fatherlessness should be understood not merely as the physical absence of fathers but as a failure to fulfill relational and educational roles. The article concludes that the Qur’anic concept of ideal fatherhood provides a strong ethical and normative framework for strengthening Muslim family resilience and addressing the crisis of fatherhood in contemporary Indonesian society